Phytochemicals, essential oils, and bioactivities of an underutilized wild fruit Cili (Rosa roxburghii) - Yang, Qiong Qiong; Zhang, Dan; Farha, Arakkaveettil Kabeer; Yang, Xiao; Li, Hua Bin; Kong, Kin Weng; Zhang, Jia Rong; Chan, Chak Lun; Lu, Wei Ying; Corke, Harold; Gan, Ren You (Elsevier, 2020)
In this study, the phytochemical and essential oil profiles, and bioactivities of an underutilized wild fruit Cili (Rosa roxburghii) were analyzed. Cili fruit was found to have higher antioxidant activities, ascorbic acid content (122 mg LAA/g DW), total phenolics (173 mg GAE/g DW), and total flavonoids (34.5 mg CE/g DW) than 11 selected common fruits and vegetables. Thirty phytochemical compounds were tentatively identified in the aqueous-ethanolic extract of Cili fruit using UPLC-QTOF-MS. Linoleic acid and 2, 2′-methylenebis (6-tert-butyl-4-methylphenol) were tentatively identified as the predominant essential oil components using GC–MS. The aqueous-ethanolic extract of Cili fruit was further tested for its in vitro bioactivities, and found it exhibited antibacterial activity against four multi-drug resistant strains of Staphylococcus aureus, and showed in vitro anti-proliferative effects against three cancer cells. Overall, the Cili fruit with diverse bioactive compounds and bioactivities can be applied in the food, nutraceutical, and cosmetic industries for the development of functional products. © 2019 Elsevier B.V.